Antimicrobial and Prebiotic Properties of Cellobiose from Sago Frond and Application as Substrate for The Production of L-Lactic Acid - Muhammad Norhelmi, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2017)
Sago palm is one of most important commodity from the state of Sarawak for the production of sago starch. The biggest challenge of sago palm plantation industry is the maturity period of sago palm is very long where it took 10 to 15 years for the sago palm to be harvestable. For addition, within the maturing process of sago palm there is no side product can be obtained from this commodity. Thus, sago frond was suggested to be alternative raw material for the production of high value product such as sugar, prebiotic ingredient, antibiotic compound, and lactic acid. Sago frond was utilized into sago frond sugar (SFS) via enzymatic hydrolysis using enzyme Celluclast 1.5L lead to the production of cellobiose (16.15%) as main product followed by glucose (9.37%). SFS was observe to contain 1.86±0.018 g/L phenolic and 0.423±0.003 g/L flavonoid compounds. SFS then purified using powdered activated charcoal to remove impurities and yeast was used to convert glucose into ethanol then remove via evaporation.